Validity and Reliability of The Verbal Aggression Scale in Junior High School Students: Exploratory and Confirmatory Factor Analysis - Suandi; Muslihati; Yuliati Hotifah (UIN Siber Syekh Nurjati Cirebon, 2026)
This study aimed to examine the construct validity and reliability of the Verbal Aggression Scale (VAS) among seventh-grade junior high school students using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Accurate measurement of verbal aggression is essential for identifying students’ behavioral tendencies and supporting evidence-based guidance and counseling interventions. This study employed a quantitative psychometric design involving 420 seventh-grade junior high school students. The instrument was an Indonesian adaptation of the Verbal Aggression Scale developed through a systematic cross-cultural adaptation process, including forward translation, back translation, expert judgment, and pilot testing to ensure linguistic and cultural appropriateness. The final instrument consisted of 20 items rated on a five-point Likert scale. Prior to factor extraction, data suitability was confirmed using the Kaiser-Meyer-Olkin (KMO) measure and Bartlett’s Test of Sphericity. The EFA results indicated that all items loaded on one dominant factor, suggesting that verbal aggression among junior high school students is primarily represented as a unidimensional construct. The CFA demonstrated an acceptable model fit, with RMSEA = 0.065, CMIN/DF = 1.931, CFI = 0.872, and TLI = 0.852. Reliability analysis showed satisfactory internal consistency, with both McDonald’s ω and Cronbach’s α exceeding 0.70. These findings provide empirical evidence that the Indonesian version of the Verbal Aggression Scale possesses adequate construct validity and reliability for assessing verbal aggression among junior high school students and supports its use as a valid assessment instrument for guidance and counseling services, educational research, and school-based intervention programs in Indonesia.